Elaboration of Furopyridine Scaffolds. Issue 11 (22nd January 2015) - Jasselin‐Hinschberger, Adeline; Comoy, Corinne; Chartoire, Anthony; Fort, Yves
Abstract: Over the past few decades, furopyridines have emerged as key structural subunits prevalent in a number of natural products and structural analogues associated with interesting biological activities. Consequently, considerable efforts have been devoted to the synthesis of these fused heterocyclic scaffolds. This review covers the main methodologies reported in the literature for the preparation of furopyridines. Abstract : This review is focused on furopyridines and especially on the different strategies that allow their synthesis.